TANTANGAN DAKWAH PADA MASYARAKAT MULTIKULTURAL DI KALIMANTAN TENGAH - Abdul Azis; Nor Muslim; Siti Zainab (Wardah, 2018)
This paper examines the challenges of da'wah to multicultural communities in three districts of Kalimantan Tengan Province. These three districts are commonly dubbed as Watersheds because they are the initial pathway for the spread of Islam in Kalimantan Tengah, at this time Muslim religion is Muslim. This paper is based on research based on interviews, FGD and documentation data. The results of the study show: The challenges of da'wah to the multicultural community in Kalimantan Tengah from internal and external factors. Internal factors come from preachers; honey; approach; methods and propaganda media. External factors including the efforts made and the weakness of the government's partisanship towards the da'wah activities that exist in the development of slow and standby propaganda are symbolic.